Parents’ Attitudes Toward and Experience of Non-Suicidal Self-Injury in Adolescents: A Qualitative Study - Fu, Xi; Yang, Jiaxin; Liao, Xiaoli; Lin, Jingjing; Peng, Yao; Shen, Yidong; Ou, Jianjun; Li, Yamin; Chen, Runsen (Frontiers in Psychiatry, 2020)
Background Non-suicidal self-injury (NSSI) is prevalent in adolescents and brings a series of serious consequences to their well-being. However, little is known about parents’ attitude towards NSSI in Chinese adolescents. The study aims to investigate the parents’ attitudes towards and perceptions of adolescents who have engaged in NSSI behaviours, and the impact of NSSI on their parents. Methods Purposive sampling was used in the study. The biological parents of adolescents with NSSI were recruited from the psychiatric ward of a tertiary hospital in China. Semi-structured interviews were conducted which contained 3 aspects, that is the history of NSSI, the process of seeking or maintaining help and the impacts on the family. Each interview typically lasted 40 to 50 minutes. All of the interviews were audio-recorded. Their responses were analysed by the thematic analysis. Results Twenty participants completed the interview, consisting of 16 mothers and 4 fathers. Three themes and 8 sub-themes were extracted: (1) the attitudes to children's NSSI behaviours (ignorance, shame, and stereotype); (2) coping strategies of parents (the initial response to adolescents’ NSSI, and the way of help-seeking); (3) the impacts on family (altered parenting and communication styles, limited personal lives, and increased psychological pressure). Conclusion The results showed that parents lack the knowledge about NSSI and its treatment and are suffering great emotional stress. It is recommended to expand the popularization of knowledge of NSSI in adolescents and more interventions adapted to China's sociocultural climate are required for the well-being of parents and NSSI in adolescents.